Demo Penolakan RUU Cipta Kerja dalam Kacamata Teori Konflik Sosiologi - Ferdi Gultom; Agus Machfud Fauzi (DOKTRINA: JOURNAL OF LAW, 2021)
RUU Cipta Kejra is part of the Omnibus Law in the ratification of many verses which are in the context of controversy. The ratification of the RUU Cipta Kerja invites conflict between workers and the government. Both parties experienced collisions, which resulted in demonstrations on 8-10 October. The demonstration involved workers and students. The demonstration was also chaotic because of the elements who carried out acts of fandalism. The purpose of this paper is to discuss the rejection of the RUU in the View of Sociological Conflict Theory. So this paper will discuss how the demonstration was carried out from a sociological perspective, particularly in sociology of law through conflict theory. This paper uses the literature study method, which data sources come from secondary sources obtained through news sources, articles, journals, and books. Then from the data obtained, it is processed and analyzed using Conflict Theory. The results of this study were demonstrations caused by conflicts between students and workers and the government. There are several factors that led to the demonstration, namely, First, communication between workers and the government. Second, there is a change in the balance in society where the workers are threatened by their human rights. Third, interests. Fourth, there is pressure from the past or unresolved problems, where the reserves of workers are not fulfilled.